Nationwide assessment of ambient monthly fine particulate matter (PM2.5) and the associations with total, cardiovascular and respiratory mortality in the United States - Austin Rau; Azar Abadi; Mark B Fiecas; Yeongjin Gwon; Jesse E Bell; Jesse D Berman (IOP Publishing, 2022)
High air pollution events spanning multiple months and caused by environmental perturbations such as droughts and wildfires are increasing in frequency, intensity and duration due to climate change. While both daily and annual exposure to fine particulate matter (PM _2.5 ) have regulatory standards in the United States, mid-scale exposure at the monthly interval remains unregulated and the public health impacts of mid-duration ambient air pollution exposure are poorly understood. These present a new public health challenge in mitigating harmful effects of persistent ambient air pollution on community health. We executed an ecological study of the associations between monthly mean PM _2.5 exposure with total, cardiovascular and respiratory mortality counts, stratified by age, sex and race, in 698 counties in the conterminous United States from 1999 to 2018. A two-stage model was used to estimate the risk and number of deaths associated with this exposure timescale reported as incidence rate ratios (IRRs) and absolute risk differences per million persons (ARDs). Increased mortality of all types was positively associated with a 10 μ g m ^−3 monthly change in PM _2.5 exposure (total mortality IRR: 1.011, 95% confidence interval (CI): (1.009, 1.013), ARD: 8.558, 95% CI: (6.869, 10.247); cardiovascular mortality IRR: 1.014, 95% CI: (1.011, 1.018), ARD: 3.716, 95% CI: (2.924, 4.509); respiratory mortality IRR: 1.016, 95% CI: (1.011, 1.023), ARD: 1.676, 95% CI: (1.261, 2.091)). Our results suggest elderly, non-black minorities and males to be the most impacted subgroups along with metropolitan and highly socially vulnerable communities. Heterogeneities in the magnitude and direction of association were also detected across climate regions of the United States. These results elucidate potential effects of monthly PM _2.5 on mortality and demonstrate a need for future health policies for this currently unregulated interval of ambient air pollution exposure.